Presence and leaching of PAHs in soils of high Andean grasslands affected by intentional burning - Vega Quispe, Anyela Pierina (2024)
Shepherds intentionally burn certain high Andean grasslands to stimulate the regrowth of grass. Nevertheless, this practice results in the generation of Polycyclic Aromatic Hydrocarbons (PAHs), which contaminate and can leach into the soil and be absorbed by plants. Ultimately, this adversely affects the livestock graze on these contaminated plants. The objective of this study was to evaluate the presence of 15 PAHs at the surface, 10, 20, and 30 cm depth, immediately and three months after burning natural grasses in Somoa, Carumas-Peru, during the year 2021. UHPLC-FLD determined PAHs, and the QuEChERS method was used to extract the PAHs from soil samples. Twelve of the 15 PAHs listed by the USEPA were found. The highest concentration was found at the surface, followed by the 10, 20, and 30 cm (759,63, 157,99, 85,86, and 68,04 ng g−1, respectively). On the other hand, Acenaphthene presented higher leaching concerning the rest of the compounds, showing 1.80 ng g−1 at 0 cm, 3.86 ng g−1 at 10 cm, 3.70 ng g−1 at 20c, and 3.44 ng g−1 at 30 cm of depth. The ∑12PAHs at the surface at T1 (first collection after burning) were 669.74 ng g−1, and T2 (second collection, three months after burning) was 759.63 ng g−1; that indicates these soils are contaminated with mean values between 600 and 1000 ng g−1. Additionally, according to the Canadian soil criteria, Fluoranthene slightly exceeded the established limits (157.99 ng g−1).